“I fear those things”: non-uptake of contraceptives, and barriers to use among adolescent girls and young women at high risk of HIV infection in Kampala, Uganda - Kawuma, Rachel; Lunkuse, Jane Frances; Ssembajjwe, Wilber; Kayesu, Ivy; Price, Matt A.; Brickley, Debbie B.; Abaasa, Andrew; Mayanja, Yunia (Frontiers in Reproductive Health, 2023)
Background Adolescent girls and young women involved in risky behaviors are vulnerable to multiple health problems, yet sexual and reproductive health services remain underutilized. We evaluated factors associated with non-uptake of contraceptives and barriers to use among adolescent girls and young women (14–24 years old) at high risk of HIV infection in an environment where contraceptives were provided at no cost. Methods We conducted a mixed methods study, utilizing data from a baseline cross sectional survey and qualitative in-depth interviews. Survey participants tested negative for pregnancy and reported willingness to use contraception. Non-uptake of contraceptives was defined as not taking contraception at any study visit (baseline and throughout the study). Logistic regression model was used to assess factors associated with non-uptake of contraceptives. We purposively selected participants for interviews to discuss their knowledge and experiences with contraceptives and make suggestions to improve uptake. Qualitative data were analyzed thematically. Results All 285 participants were included in the analysis. Out of the 285 participants 127 were not using contraceptives and of the 127, 44 (34.6%) did not take up any method throughout the study while 43 of the 83 remaining participants (who took up a method) chose male condoms only. Non-uptake of contraceptives was less likely among older women (20–24 years) (aOR = 0.32, 95% CI 0.16–0.89) compared to younger women (less than 20 years). Qualitative data showed that concerns about future fertility, fear of associated side effects and influence from close relations contributed to non-uptake of contraception. Conclusion Non-uptake of contraceptives was common despite the promotion and provision of contraceptives in the context of a research study mainly because adolescents lack autonomy while making contraceptive decisions. Identifying and addressing their concerns and continued counselling on contraceptive use alongside condom promotion may improve uptake and utilization of contraceptives.